2018
DOI: 10.3390/nano8030140
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of E. coli Growth by Nanodiamond and Graphene Oxide Enhanced by Luria-Bertani Medium

Abstract: Nanodiamonds (NDs) and graphene oxide (GO) are modern carbon-based nanomaterials with promising features for the inhibition of microorganism growth ability. Here we compare the effects of nanodiamond and graphene oxide in both annealed (oxidized) and reduced (hydrogenated) forms in two types of cultivation media—Luria-Bertani (LB) and Mueller-Hinton (MH) broths. The comparison shows that the number of colony forming unit (CFU) of Escherichia coli is significantly lowered (45%) by all the nanomaterials in LB me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…The bacterial strains used in this study are listed in Table 1. All Escherichia coli strains were grown at 37 • C in Luria-Bertani broth (Jira et al, 2018). The spores of S. pogona and S. spinosa and their derivatives were activated in complete synthetic medium (per liter: 10 g of glucose, 45 g of trypticase soy broth, 9 g of yeast extract, and 2.2 g of MgSO 4 •7H 2 O).…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…The bacterial strains used in this study are listed in Table 1. All Escherichia coli strains were grown at 37 • C in Luria-Bertani broth (Jira et al, 2018). The spores of S. pogona and S. spinosa and their derivatives were activated in complete synthetic medium (per liter: 10 g of glucose, 45 g of trypticase soy broth, 9 g of yeast extract, and 2.2 g of MgSO 4 •7H 2 O).…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…This finding may represent an undiscovered, novel and important drug resistance mechanism by which A. baumannii escapes β-lactam antibiotics through actively truncating PBP1b under antibiotic pressure. (3) The expression of truncated PBP1b also increases in MH culture medium, which may be related to the ionic strength of different media (Jira et al, 2018). At present, very few studies have investigated the function of PBP1b in A. baumannii strains.…”
Section: Discussionmentioning
confidence: 99%
“…NDs also have an intrinsic bactericidal activity [63,64]; Wehling et al showed that the viability of E. coli is nearly 100% compromised after only 15 minutes post-exposure to NDs. This elevated rate of bacteria death was the consequence of a great intake of the NDs by the bacteria, causing deformation of the bacteria cell.…”
Section: Nanodiamonds In Antipathogenic Systemsmentioning
confidence: 99%